النبر ودوره الدلالي في توجيه مفردات اللغة: دراسة تطبيقية - Al Abdullah, Murad H. (Journal of Arabic Education and Linguistics, 2025)
Language is not merely a means of communication between individuals or specific groups; rather, it constitutes a comprehensive system composed of phonetic components, morphological structures, syntactic formations, and semantic elements that collectively work to shape overall meaning. Through these components, phonological phenomena emerge, playing a fundamental role in determining linguistic meanings. Among these phenomena is the variation in the intensity of pronunciation—whether rising or falling—which contributes to defining the general meaning of sentences and phrases. This is known as phonetic stress, which refers to the emphasis placed on specific syllables within words or sentences. Stress is characterized by its ability to draw attention to certain meanings or to create distinctions in meaning, whether within similar words or in sentence-level contexts.